"Open Your Gates to Us, Wide and Trustingly": The Foundation of Special Propaganda in the Red Army. Issue 4 (1st October 2020) - Cheravitch, Joe
ABSTRACT: The eventual decision by the Soviet military to dedicate a force to 'special propaganda' (or spetsprop ) was sparked by disappointments in the pre-war campaigns, from the Far East to Finland between 1938 and 1940. Special propaganda represented one of the earliest forms of Soviet asymmetric warfare, one that would even outlive the Soviet state. Stalin's mass purge of the Soviet military, however, deprived special propaganda of the kind of officers it needed most: linguists and foreign area experts. The Soviet experience evidences the probable paradox that affects many totalitarian regimes' efforts to influence audiences beyond their control: although propaganda is a critical element of their survival, their inherent insularity precludes the ability to understand the populations they seek to influence.